Influence of Price, Service Quality, and Promotion at Shipping Lines Company (ONE) on Customer Decisions - Firyaal Nadhira; Nisrina Fhatin; Honny Fiva Akira Sembiring; Sarovah Widiawati (Jurnal Ilmu Multidisiplin, 2025)
In international trade activities, the role of a shipping company is very important. Shipping acts as a means of transportation in moving goods from one place to another. This study purpose is to determine and analyze the influence of price, service quality, and promotion, which will have a direct effect on ONE's customer decisions on an ongoing basis. The sample population in this study were the users of the shipping company (ONE). There were 105 respondents. The analysis method used in this research is quantitative descriptive method. The method the author chose for data collection was to conduct a survey in the form of a questionnaire. The results proved of this research simultaneously had a positive and significant impact on ONE's customer decisions.